THE OPİNİONS OF UNİVERSİTY STUDENTS ABOUT NUTRİTİON SERVİCES AT UNİVERSİTY CANTEENS (Third Sector Social Economic Review, 2013)
This research investigates the opinions of university students about nutrition services at university canteens. The data have been collected from 491 students: 286 female, 205 male. In the data collection stage a survey, which investigates the purchasing frequency of food and beverages and the students’ opinions about the nutrition services, has been conducted. As a result of statistical analysis, it is found out that the students prefer to go to the university canteen as a second choice (%32.4) and they prefer to eat toasted sandwich, bagel/pastry, potato chips, chocolate and biscuits once or twice a week; among the beverages they purchase most frequently tea, ayran, fruit juice and Nescafe respectively. When the students’ opinions about nutrition services at the canteens are examined it is ascertained that the students generally are not satisfied (3.3±0.63) with the canteen services. Besides, only 40.2% of the female students think that the canteen services are sufficient. On the other hand, the percentage of the male students who think that the canteen services are satisfactory is 53, 7%.The difference between the opinions of female and male students is statistically significant (p
Keywords: adolescent; canteen; nutrition; consumer satisfaction